2014
DOI: 10.4149/neo_2014_052
|View full text |Cite
|
Sign up to set email alerts
|

Co-mutated pathways analysis highlights the coordination mechanism in glioblastoma multiforme

Abstract: The mutation of cancer represents a high heterogeneity characteristic, setting a big obstacle in the mechanism study of it. In this study, we explored the distributions of mutated genes in pathways in glioblastoma multiforme (GBM), and constructed networks of co-mutated pathway pairs under the false discovery rate (FDR) control. By comparing the mutation frequencies, a total of 50 mutated genes were screened with the frequency > 3, and TP53, PTEN, and EGFR were the top 3 genes. By KEGG enrichment, 18 pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…By KEGG analysis, we found that these DEGs were enriched in the signaling pathways such as cell cycle, p53 signaling pathway, retrograde endocannabinoid signaling and dopaminergic synapse. A previous study showed that the cell cycle and p53 signaling pathways co‐mutated in GBM (Wei, Wang, & Zhao, ). Notably, the p53 signaling pathway exerts an important role in glioma pathogenesis (Stegh & DePinho, ).…”
Section: Discussionmentioning
confidence: 99%
“…By KEGG analysis, we found that these DEGs were enriched in the signaling pathways such as cell cycle, p53 signaling pathway, retrograde endocannabinoid signaling and dopaminergic synapse. A previous study showed that the cell cycle and p53 signaling pathways co‐mutated in GBM (Wei, Wang, & Zhao, ). Notably, the p53 signaling pathway exerts an important role in glioma pathogenesis (Stegh & DePinho, ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, GABAergic synapse, Cholinergic synapse, and Glutamatergic synapse may be common pathways for MDD and GBM. Retrograde endocannabinoid signaling has been shown to be related to the pathophysiological mechanisms of MDD and GBM [ 32 , 33 ]. Pathways in cancer, Chemokine signaling pathway is also a common pathway when using genomics enrichment.…”
Section: Discussionmentioning
confidence: 99%
“…A switch to PTEN-dependent signalling is often a feature of more advanced tumours, possibly due to chromosome 10 loss of heterozygosity or resistance selection due to drug-induced inhibition of other proliferative pathways [214,233,234,245]. In this way, upregulation of non-PIP oncogenic signalling networks may work in concert with PTEN deletions to generate a malignant phenotype and this may explain the mixed success so far in clinical trials of molecules that target solely upstream components of the receptor-PI3K signalling axis [246][247][248][249][250][251]. While PTEN is very well studied in glioma, other enzymes that can amplify PI3K signalling such as constitutively activating PIK3CA mutations [147,212,252,253] also feature in many patients with this disease and indeed other neurological cancers including anaplastic oligodendrogliomas, anaplastic astrocytomas and medulloblastomas [254,255].…”
Section: Activated Pi3k Signalling: Overgrowth Versus Gliomamentioning
confidence: 99%